OP0137 Complete Survival and Disease Amelioration in MRL/LPR Mice Following Therapeutic Administration of an Oral Retinoic Acid Receptor-Related Orphan Receptor Gamma T [RORGT] Inverse Agonist INV-17: A Promising Safe & Efficacious Novel Lupus Treatment. (9th June 2015) - Gaweco, A.; Matthews, K.; Palmer, S.; Shamilov, R.; Adam, K.; Elia, A.; Clybouw, C.; Windsor, W.; Nomeir, A.; Stouch, T.; Ginzler, E.; Tilley, J.
Abstract : Background: There are limited treatment options currently available for patients with systemic lupus erythematosus [SLE] and lupus nephritis [LN] providing modest therapeutic benefit in some patients associated with substantial toxicities. T helper 17 [TH 17] cells and their production of TH 17 cytokines (IL-17A, IL-17F) play a critical role in the pathogenesis of several autoimmune diseases including SLE and LN. Increased TH 17 cytokine expression is observed in lupus-prone mouse models and in lupus patients associated with worsening disease. RORgT is a nuclear hormone receptor that specifically regulates TH 17 cells by acting as a control switch for TH 17 differentiation, function and cytokine production. Successful drug development efforts led to the discovery of several proprietary novel chemical scaffolds of the INV-17 portfolio of small molecule RORgT inverse agonists. Select INV-17 compounds demonstrate potent in vitro pharmacological effects against TH 17 cells and cytokines, optimal drug-likeness & pharmacokinetic properties and superior therapeutic efficacies in preclinical autoimmune models of rheumatoid arthritis and multiple sclerosis. 1, 2 Objectives: The in vivo treatment efficacy of INV-17 was assessed in this initial pilot study prior to a larger study group in lupus-prone MRL/ lpr mouse model to establish the preclinical Proof of Concept of a novel oral INV-17 RORgT inverse agonist. Methods: Lupus-prone MRL/ lpr mice spontaneously develop disease. Upon disease-onset, mice with a proteinuria score >2 (Scale: 0-3) were randomized to receive 6-wk of therapeutic treatment dosing with INV-17 per oral gavage at 2 mg/kg (n=4) versus controls receiving vehicle alone (n=7). Results: Complete survival was observed in 100% of INV-17 treated mice compared to only 57% survival in vehicle-treated mice after 6-wk of dosing [Figure ]. Successful disease amelioration following INV-17 treatment was observed as early as treatment day 11 with a significant reduction in mean proteinuria score (1.25±0.5; p=0.03) versus vehicle controls (2.17±0.8). Lower mean proteinuria area under the curve [AUC] score of 17.3 in the INV-17 group contrasted to those in the vehicle group with 22.1. INV-17 was well tolerated and INV-17-treated mice were unremarkable with optimal body condition scores of Grade BCS3. Conclusions: The superior safety and therapeutic efficacy data following 6-wk treatment of an oral small molecule INV-17 clinical candidate compound provide the first report establishing the therapeutic efficacy in lupus following pharmacological intervention with an RORgT inverse agonist. This compelling evidence supports advancing INV-17 into IND-enabling development stage and highlights the potential promise of INV-17 as a safe & efficacious novel treatment for lupus. References: Gaweco et al. 2014 Arthritis Rheum. 66[11]: S137. Gaweco et al. 2013 J.Neurol.Sci. 333: 362-363. Disclosure of Interest: A. Gaweco Employee of: Innovimmune Biotherapeutics, K. Matthews Employee of: Innovimmune Biotherapeutics, S. Palmer Employee of: Innovimmune Biotherapeutics, R. Shamilov Employee of: Innovimmune Biotherapeutics, K. Adam Employee of: Innovimmune Biotherapeutics, A. Elia Employee of: Innovimmune Biotherapeutics, C. Clybouw Employee of: Innovimmune Biotherapeutics, W. Windsor Employee of: Innovimmune Biotherapeutics, A. Nomeir Employee of: Innovimmune Biotherapeutics, T. Stouch Employee of: Innovimmune Biotherapeutics, E. Ginzler Consultant for: Innovimmune Biotherapeutics, J. Tilley Employee of: Innovimmune Biotherapeutics